Recurrent bacterial meningitis. - Dias, Andrea (2010)
Recurrent bacterial meningitis (RBM) is an unusual entity and usually poses a considerable diagnostic challenge. Different conditions can predispose for recurrence of episodes and the isolated pathogen can guide the diagnosis. The aim of this study was to characterize all RBM admitted to our tertiary paediatric hospital.Retrospective analysis of the medical records of all children with RBM, between January 1994 and December 2007 (14 years).During this period, 107 children with bacterial meningitis (BM) were admitted. Among those, 10 (9.3%) had more than 1 episode of BM. Five (4.7%) had cerebrospinal fluid shunt. In the other 5 (4.3%), 11 episodes of BM were identified. S. pneumoniae was isolated in the majority of episodes (4) followed by N. meningitis (2). An anatomical defect, namely post-traumatic CSF leakage, was present in 3 children and S. pneumoniae was isolated in all. A predisposing condition has not yet been identified in 2 children and no anatomical defect or immunodeficiency was found despite full investigation.It was identified a high proportion of RBM compared to other series, that could be explained by the fact of being a tertiary hospital. An anatomical defect was the most frequent cause and S. pneumoniae the most frequent bacteria. In cases without an obvious predisposing condition an exhaustive evaluation, including search for anatomical and immunological defects, was performed but no changes were identified.